2003
DOI: 10.1145/960492.960539
|View full text |Cite
|
Sign up to set email alerts
|

How shall we assess this?

Abstract: Increased class sizes are forcing academics to reconsider approaches to setting and marking assessments for their students. Distributed and distance learning are creating some of the biggest changes. Some educators are embracing new technologies but others are more wary of what they do not know. In order to address this issue it is first necessary to investigate the types of assessment currently in use and the perceptions that are held by academics with and without experience of the new technologies that are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Contact Publisher@InformingScience.org to request redistribution permission. Ala-Mutka (2005) provides a critique of a number of automated assessment initiatives; Carter et al report on the results of an international teaching staff survey of automated assessment (Carter et al, 2003), and Rosenthal (2004) showed a clear preference for automated assessment in blind tests. Students can benefit from instant feedback, consistent and impartial marking, and the ability to progress at their own pace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact Publisher@InformingScience.org to request redistribution permission. Ala-Mutka (2005) provides a critique of a number of automated assessment initiatives; Carter et al report on the results of an international teaching staff survey of automated assessment (Carter et al, 2003), and Rosenthal (2004) showed a clear preference for automated assessment in blind tests. Students can benefit from instant feedback, consistent and impartial marking, and the ability to progress at their own pace.…”
Section: Introductionmentioning
confidence: 99%
“…Many people still believe that 'automated assessment' and 'multiple choice tests' are effectively synonymous (Carter et al, 2003), and even when shown how freetext questions can be marked, refuse to believe that they can assess the ineffable qualities they look for when marking by hand, in the same way as many people used to believe that computers could never play chess as well as a human being because of a lack of strategic vision and human intuition. In the light of the experiences we have described here and the extremely positive feedback we have received, we hope that this paper will help to convince others to try to use automated assessment in their own courses.…”
mentioning
confidence: 99%
“…In his earlier work, Ercole et al (2002) studied collusion in a comparative empirical study using multiple choice questions in face-to-face and online examinations. It is one of the major security threats (Laubscher et al 2005) which challenges the validity of online examinations (Carter et al 2003). It can be classified in the following categories based on its occurrence in different scenarios (Ullah et al 2016…”
Section: Background and Related Work 21 Academic Dishonesty And Collmentioning
confidence: 99%
“…First, students often collaborate with peers and teaching assistants while working on the assignments. While we encourage students to ask questions and collaborate, it is difficult point out which part of the code a student has figured out himself and which part he or she could not have completed without help from the peers or teachers (Carter et al, 2003). For these reasons, an exam, an open-book exam in our case, can be seen as a reasonably reliable way to assess a CS exam.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these benefits from the student's point of view, practical programming in computer-based environment provides teachers a way of evaluating students' application and problem-solving skills in a semi-or fully automatic fashion (computer-based or computer aided assessment, see, Carter et al, 2003;Russell et al, 2003). Yet, final exams in CS1 are often conducted with penand-paper.…”
Section: Introductionmentioning
confidence: 99%